2015
DOI: 10.1111/dom.12570
|View full text |Cite
|
Sign up to set email alerts
|

Mixed meal ingestion diminishes glucose excursion in comparison with glucose ingestion via several adaptive mechanisms in people with and without type 2 diabetes

Abstract: Adding protein and fat macronutrients to glucose in a mixed meal diminished glucose excursion. This occurred in association with increased β-cell function, reduced insulin clearance, delayed gastric emptying and augmented glucagon and GIP secretion. This suggests that the macronutrient composition regulates glycaemia through both islet and extra-islet mechanisms in both healthy subjects and in subjects with T2D.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(49 citation statements)
references
References 40 publications
3
45
1
Order By: Relevance
“…This occurred in association with increased β-cell function, reduced insulin clearance, delayed gastric emptying and augmented glucagon and GIP secretion [12]. These findings may be in line with our observation that post-prandial low glycemia was frequently observed more after meal ingestion (58 g carbohydrates) than after 75 g glucose ingestion in young women.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…This occurred in association with increased β-cell function, reduced insulin clearance, delayed gastric emptying and augmented glucagon and GIP secretion [12]. These findings may be in line with our observation that post-prandial low glycemia was frequently observed more after meal ingestion (58 g carbohydrates) than after 75 g glucose ingestion in young women.…”
Section: Discussionsupporting
confidence: 88%
“…Adding protein and fat macronutrients to glucose in a mixed meal diminished glucose excursion as compared with the same amount of glucose challenge alone [12]. This occurred in association with increased β-cell function, reduced insulin clearance, delayed gastric emptying and augmented glucagon and GIP secretion [12].…”
Section: Discussionmentioning
confidence: 99%
“…Our analysis confirmed the results of previous studies, which showed that GLP-1 and GIP secretion are stimulated by all three macronutrients, carbohydrate, protein and fat. [25][26][27][28] Although our study was not designed to test the effects of individual macronutrients on incretin hormone secretion, our data indicate that GIP secretion is dependent on total energy intake and possibly on energy intake by protein and fat, as it was largest after lunch, which had a higher total caloric content and highest caloric provision from protein and fat. In contrast, no such dependency was evident for energy intake by carbohydrate or for GLP-1 secretion.…”
Section: Dpp-4 Inhibition Differs Between Dpp-4 Inhibitors Although mentioning
confidence: 94%
“…GLP-1, mainly secreted by intestinal enteroendocrine L cells in the ileum can inhibit the pancreas islet a cells, thus improving postprandial glycemia and insulin resistance [85]. GIP, mainly secreted by K cells of the duodenum and jejunum, plays an indispensable role in improving postprandial glycemia and insulin resistance with the function of GLP-1 by stimulating the pancreas islet b cells [86]. Intestinal motility is modulated by multiple hormones.…”
Section: Gastrointestinal Motility Adjustmentmentioning
confidence: 99%